Volatilization behavior of tin during carbothermic reduction of tin-bearing middling to recover tin - Jing J.; Guo Y.; Chen F.; Zheng F.; Yang L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A new method for selecting reducing agent was proposed in this study. This study dedicated to recovery of tin from tinbearing middling by carbothermic reduction. Volatilization behavior of tin during carbothermic reduction was systematically studied, including the tin volatilization thermodynamics and kinetics, the selecting method of reducing agent, the effects of reducing agent, reduction temperature and effect of time on the tin volatilization rate. The thermodynamic results showed that the SnO2 was reduced to SnO by controlling CO% in the range of 9%~15%, and then volatilized as SnO. The reduction efficiency and the reaction capability with CO2 of three reducing agent were investigated, which indicated tin volatilization was close in nature to the reductant, and it was beneficial to the volatilization by using the coke powder. The experiment results show that the volatilization ratio of tin can reach more than 81.34% when the coke powder is used as the reducing agent at 900°C for 2h. The kinetic of tin volatilization during the reduction roasting process showed that the reaction was controlled by the interface chemical reaction and the activation energy of the reaction was 44.66 kJ/mol.